Determinasi Kualitas Laba dengan Ukuran Perusahaan sebagai Variabel Moderasi pada Perusahaan Subsektor Makanan dan Minuman di BEI tahun 2019-2023 - Devi Masitha, Hani; Listiorini Listiorini (Jurnal Ekonomi Manajemen Akuntansi, 2025)
A competitive company is basically a company that is able to maintain consistency and stability of profits in various business activities, without having to commit acts of fraud that can harm internal and external parties. Achieving high-quality profits is an important indicator of the company's sustainability because it reflects management's ability to effectively manage assets, resources, and business strategies. In the context of this study, the main focus is directed to the effect of leverage, liquidity, and profitability on the quality of profit with the size of the company as a variable of moderation. The study was conducted on food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023. The research method used is quantitative with analytical descriptive approach. The selection of samples was carried out by purposive sampling technique so that 25 companies were obtained as samples with a total of 125 financial statement data for five years of observation. Based on the results of the analysis, it was found that leverage, liquidity and profitability have a negative and significant influence on the quality of profit. This finding shows that the higher the three variables, the quality of profit actually decreases. Furthermore, the results revealed that the size of the company is not able to moderate the relationship between leverage, liquidity, and profitability to the quality of profit.